Oxidative stress leads to inhibition of mevalonate pathway in Hevea brasiliensis - Krishnakumar R; Annamalainathan K; Jacob J; Simon S P (National Symposium on Metabolic Pathway Studies for Crop Improvement December 13-15, 2001. p68 : Abstracts, 2001)
Mevalonate pathway is widely present in both plant and animal kingdoms. There are over 2000 species of latex producing plants that have this pathway. Hevea brasiliensis is the only major source of natural rubber (cis-poly isoprene). The conversion of mevalonate into poly isoprene occurring in the bark tissue of this tree species is a extremely energy consuming process. Although this pathway is inherently present and active in Hevea, in a small percentage of the trees the mevalonate pathway gets completely inhibited resulting in a physiological disorder called tapping panel dryness(TPD) syndrome. Our studies reveal that lack of availability of carbohydrates was not a limiting factor but there was inadequate supply of ATP for the conversion of sugars into isoprene in TPD affected trees. We further show that although the ATP status was small, the rate or respiration was large in TPD affected tissues. This increase in respiration was largely due to an increase in the alternative oxidase (AO) activity which is far less efficient than the normal cytochrome pathway for synthesizing ATP. In conclusion we show that the complete inhibition of mevalonate pathway noticed in some Hevea trees termed TPD is essentially an expression of acute oxidative stress.
Keywords: Hevea brasiliensis; Inhibition; Mevalonate pathway; Oxidative stress; TPD